Separation of five flavone glycosides including two groups with similar polarities from Dracocephalum tanguticum by a combination of three high‐speed counter‐current chromatography modes. Issue 2 (16th November 2021) - Chen, Tao; Yang, Xue; Wang, Shuo; Shen, Cheng; Li, Hongmei; Wei, Yangfei; Yan, Shuping; Song, Zhibo; Yang, Fengmei; Liu, Yarong; Hai, Ping; Li, Yulin
Abstract: The separation of compounds with similar polarities is challenging. In the present study, five flavone glycosides, including two groups with similar polarities, were obtained from Dracocephalum tanguticum by three high‐speed counter‐current chromatography modes, including flow rate conversion mode, recycling mode, and heart‐cut mode. With flow rate conversion mode, compounds 3 and 4 with similar polarities and compound 5 were separated by high‐speed counter‐current chromatography with ethyl acetate/methanol/water (5.0% acetic acid) (8:2:10, v/v) system. The flow rate was controlled as: 1.8 mL/min for 0–160 min, 2.2 mL/min for 160–200 min, and 2.5 mL/min for 200–400 min. However, compounds 1 and 2 with similar polarities were not separated due to the similar distributive properties. Then, a recycling and heart‐cut mode were introduced to improve the separation efficiency. The heart‐cut mode was introduced in the second and third cycles, and compounds 1 and 2 were well separated in the fourth cycle. Consequently, five flavone glycosides, including two groups with similar polarities were obtained and identified as cosmosiin (1), pedaliin (2), quercetin‐3‐ O ‐rutinoside (3), pedaliin‐6''‐acetate (4), and sorbifolin‐6‐ O ‐ β ‐glucopyranoside (5). The current strategy provides a reference for separating compounds with similar polarities from a crude sample.